Characterization of pre-transplant psychosocial burden in an integrated national islet transplant program. Issue 2 (3rd March 2020) - Liew, Aaron YL; Holmes-Truscott, Elizabeth; Flatt, Anneliese JS; Bennett, Denise; Crookston, Robert; Pimkova, Mirka; Birtles, Linda; Casey, John; Pernet, Andrew; Wood, Ruth C; Choudhary, Pratik; Forbes, Shareen; et al.
ABSTRACT: The psychological burden experienced by people with diabetes prior to islet transplantation is recognized but has not been studied comprehensively, especially in relation to glycemia. Therefore, we conducted a rigorous pre-operative psychosocial profile of UK islet transplant recipients, and compared groups with higher/lower HbA1 c to test the null hypothesis that pre-transplant hypoglycemia awareness and psychosocial burden would not be related to baseline HbA1 c in this high-risk cohort. Pre-transplant, recipients (n = 44) completed validated hypoglycemia awareness questionnaires and generic/diabetes-specific measures of psychological traits and states. Scores were compared in groups, dichotomized by HbA1 c (≤8% versus >8%). Participants were aged (mean±SD) 53 ± 10 years; 64% were women; with HbA1 c 8.3 ± 1.7%. Median rate of severe hypoglycemia over the preceding 12 months was 13 events/person-year and 90% had impaired awareness of hypoglycemia (Gold/Clarke score ≥4). Participants had elevated fear of hypoglycemia (HFS-II Worry), impaired diabetes-specific quality of life (DQoL) and low generic health status (SF-36; EQ-5D). One quarter reported scores indicating likely anxiety/depression (HAD). Dispositional optimism (LOT-R) and generalized self-efficacy (GSE) were within published 'norms.' Despite negative perceptions of diabetes (including low personal control), participants were confident that islet transplantation would help (BIPQ). Hypoglycemia awareness and psychosocial profile were comparable in lower (n = 24) and higher (n = 20) HbA1 c groups. Islet transplant candidates report sub-optimal generic psychological states (anxiety/depressive symptoms), health status and diabetes-specific psychological states (fear of hypoglycemia, diabetes-specific quality of life). While their generic psychological traits (optimism, self-efficacy) are comparable with the general population, they are highly optimistic about forthcoming transplant. HbA1 c is not a proxy measure of psychosocial burden, which requires the use of validated questionnaires to systematically identify those who may benefit most from psychological assessment and support.